Asia-Europe: The third link - Jeremie Cohen-Setton; Jean Pisani-Ferry (Bruegel, 2008)
[Introduction] The prevailing view of the world economy is strikingly polarised. Analyses of macroeconomic linkages and transmission channels routinely represent the world with the US at the centre and other regions, among which Asia and Europe, at the periphery. Asia and Europe are obviously regarded as important players, but mainly in interaction with the US rather than with each other. In recent assessments of the short-term economic outlook, the US is still widely seen as the driving force behind the global business cycle. The same bias has been apparent in discussions about exchange rates, as China, Japan, and the euro area have been discussing the relationship between their currencies and the US dollar separately without paying much attention to their bilateral relationships until the end of 2007. From innovation leadership to the issuance of the world's premier currency there are several objective reasons why the US economy still plays a leading economic role in the world and our intention is not to dispute this reality. But this reality cannot justify retaining an outdated or distorted view of international interdependence. Policymakers in Asia and Europe need to take the full measure of the international role of their economies and of their corresponding global responsibilities. Our aims in this paper are: - to provide an objective assessment of the weight and interdependence of the major regions; - to investigate the Asia-Europe relationship in the context of the world economy; - to contribute to current discussions about the global repercussions of the financial turmoil; - to shed light on the implication of growing cross-border assets and liabilities between the three regions. To this end we adopt a deliberately stylised view of the world economy and look at broad regions instead of countries. This overlooks many disparities within regions but has the advantage of allowing a consistent and tractable approach to trade and financial linkages in the context of scarce global supply of energy and food commodities. The paper is organised as follows. We start in section 2 from a decomposition of the world economy into four regions (North America, East Asia, Europe and the Rest of the World) and we assemble a number of stylised facts about their size and openness. We turn to bilateral linkages in section 3, looking separately at trade and financial linkages to investigate how the three main regions interact with each other. We take up the transmission of shocks in section 4 and the implications of exchange-rate adjustments in section 5. Section 6 offers conclusions. Sections 2 and 3 are mainly descriptive and can be skipped by uninterested readers.
Keywords: 330